Occurrence and duration of phenological phases of Freesia x hybrida grown at different planting dates - Santilli, Melisa; Bas-Nahas, Santiago Sebastián; Medrano, Norma Nelly (Sociedade Brasileira de Floricultura e Plantas Ornamentais (SBFPO), 2023)
Freesia (Freesia x hybrida) is one of the most cultivated species of cut flowers, ranking sixth in the international market. Pheno- logical processes occurring during the crop cycle are controlled by endogenous mechanisms and the environment, which in turn influence the duration and occurrence of the development phases. This study aimed to analyze the effect of planting dates (Feb 15, March 19, April 16, May 21, and June 21, 2021) on the occurrence and duration of the development phases of two freesia varieties (Blue Bayou and Yvonne). The trial was conducted in a high tunnel. The crop cycle was divided into vegetative, reproductive, and senescence phases. The number of leaves was counted daily. The development phases were significantly shortened with the delay of planting. The vegetative phase ranged between 2269.78 ± 19.22 and 736.50 ± 19.22 GDD for Blue B., and between 1864.48 ± 19.22 and 667.09 ± 19.22 GDD for Yvonne. The reproductive phase lasted 459.50 ± 20.99 and 379.51 ± 20.99 GDD for Blue B., 461.43 ± 20.99 and 487.29 ± 20.99 GDD for Yvonne. The senescence phase was shortened with delayed planting dates only for Yvonne. Plants cultivated at later dates (May 21, and June 21), and consequently exposed to increased photoperiod, had a lower number of leaves at flowering (7.85 ± 0.10) and were less exposed to inductive temperatures than plants cultivated earlier. The transition to the reproductive phase was determined by the interaction between photoperiod, temperature and plant age.